ELECTROCHEMICAL BEHAVIOR OF 1,3-DITHIENYL AND DIFURYL PROPENONE DERIVATES: PART I - BROVELLI,FRANCISCO (Sociedad Chilena de Química, 2003)
A series of heterocyclic alpha,beta´-unsaturated ketones containing thiophene and furan rings has been synthesized. By ab-initio methods the geometries have been optimized and the electronic density distributions of neutral molecules were determined. To that the Hartree Fock (HF 6-31G*) calculations base were used. The electronic density distribution did not depend on the heteroatom type, however, there is a dependence of the group that acts as bridge. Moreover, the oxidation-reduction potentials of the molecules were determined by cyclic voltammetry on platinum electrodes. The electrochemical oxidation was irreversible and showed asymmetric peaks. This was explained by the simultaneous oxidation of the heterocyclic rings and the functional groups acting as bridge. The reduction of these species involves only the carbonyl group